The in vitro biological activity of Lepidium meyenii extracts - Valentová, K; Buckiová, D; Kren, V; Peknicová, J; Ulrichová, J; Simánek, V (Cell biology and toxicology, 2006)
The biological activity of methanolic and aqueous extracts from dehydrated hypocotyls of Lepidium meyenii (Brassicaceae, vernacular name "maca"), was studied on rat hepatocytes and human breast cancer MCF-7 cells. The extracts did not exhibit cytotoxicity in hepatocyte primary cultures up to 10 mg/ml as measured by the MTT viability test, and lactate dehydrogenase (LDH) and aspartate aminotransferase (AST) leakage. Moreover, after 72 h, extracts inhibited LDH and AST leakage from the hepatocytes. When hepatocytes were intoxicated by t-butyl hydroperoxide, neither extract prevented oxidative damage. Both extracts showed weak antioxidant activity in the DPPH radical scavenging test with IC(50) values of 3.46 +/- 0.16 and 0.71 +/- 0.10 mg/ml, for aqueous and methanolic extracts, respectively. Thus, the observed effect on spontaneous enzyme leakage is probably mediated through mechanisms other than antioxidant activity. Both methanolic and aqueous extracts have shown estrogenic activity comparable with that of silymarin in MCF-7 cell line. Maca estrogenicity was exhibited in the range from 100 to 200 mug of extract per ml. The findings in the present study show that maca does not display in vitro hepatotoxicity. In contrast, a slight cytoprotective effect, probably not mediated by antioxidant capacity, was noted. Maca extracts exhibited estrogenic activity comparably to the effect of silymarin in MCF-7 cells.
Keywords: kultivované buňky; nádorové buněčné linie; Hepatocytes; Rats; Steroids; Breast Neoplasms; estrogeny; Biphenyl Compounds; Fatty Acids; Rats, Wistar; mužské pohlaví; Cell Proliferation; Cell Line, Tumor; rostlinné extrakty; krysa rodu Rattus; bifenylové sloučeniny; Cells, Cultured; steroidy; hepatocyty; preklinické hodnocení léčiv; Picrates; zvířata; Humans; Lepidium; Estrogens; Drug Evaluation, Preclinical; proliferace buněk; nádory prsu; mastné kyseliny; pikráty; Hydrazines; potkani Wistar; Plant Extracts; hydraziny; lidé; Male; Animals